Thermophoresis and thermal radiation with heat and mass transfer in a magnetohydrodynamic thin-film second-grade fluid of variable properties past a stretching sheet - Khan, Noor Saeed; Gul, Taza; Islam, Saeed; Khan, Waris (European physical journal plus, 2017)
. The influences of thermophoresis and thermal radiation of a magnetohydrodynamic two-dimensional thin-film second-grade fluid with heat and mass transfer flow in the presence of viscous dissipation past a stretching sheet are analyzed. The main focus of the study is to discuss the significant roll of the fluid variable properties like thermal conductivity and viscosity under the variation of the thin film. The thermal conductivity varies directly as a linear function of temperature showing the property that expresses the ability of a material to transfer heat, and the viscosity is assumed to vary inversely as a linear function of temperature showing that viscous forces become weak at increasing temperature. Thermophoresis occurs to discuss the mass deposition at the surface of the stretching sheet while thermal radiation occurs, especially, at high temperature. The basic governing equations for the velocity, temperature and concentration of the fluid flow have been transformed to high nonlinear coupled differential equations with physical conditions by invoking suitable similarity transformations. The solution of the problem has been obtained by using HAM (Homotopy Analysis Method). The heat and mass transfer flow behaviors are affected significantly by the thin film. The physical influences of thin film parameter and all other parameters have been studied graphically and illustrated. The residual graphs and residual error table elucidate the authentication of the present work.